Enhancing Organizational Effectiveness through Performance Management: A Focus on Educational Institutions - Zueva Oksana (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
Performance management (PM) has evolved into a critical organizational process that supports the alignment of individual and team performance with strategic objectives. This paper explores the concept of performance management, drawing on established literature to examine its role in improving organizational effectiveness, employee development, and institutional performance. Particular attention is given to the application of PM in educational settings, where it contributes to teaching quality, staff motivation, and student outcomes. The paper also reviews key components of an effective PM system, including goal alignment, continuous feedback, and performance appraisal. While acknowledging certain non-financial limitations, the study highlights the overall benefits of PM and proposes practical recommendations for implementing sustainable and transparent systems in educational institutions.